Mood and Anxiety Symptoms, Psychological Distress, and Life Satisfaction: Differential Associations between Patients with Anxiety and Depression - Fatima, Shameem; Raazia, Ain Ul (Applied Psychology Review, 2025)
Guided by tripartite model of Clark and Watson, the study is planned to examine the differential association of anxiety symptoms with life satisfaction, and psychological distress in patients with anxiety and depression. Using correlational research design, an equally distributed sample of (N = 232) diagnosed patients of Anxiety and Depression, between the age range of 21 to 61 were selected using purposive sampling technique. Anxiety symptoms, life satisfaction, and psychological distress scales were used as assessment measures. Descriptive analysis and group differences revealed significant variations, showing high score in anxiety patients, i.e., on anxious arousal, anxious symptoms, and psychological distress. The patients with depression scored higher on depressive symptoms, anhedonic depression and lower levels on life satisfaction. Furthermore, both anxiety symptom subscales were positive predictors of psychological distress only for patients with anxiety. However, two subscales of depressive symptoms were significant negative predictors of life satisfaction for patients with depression only. The results support the tripartite model of mood anxiety symptoms. The results have clinical and research implications providing valuable insights for interventions with anxiety and depression patients to reduce psychological distress and improve wellbeing.